2014
DOI: 10.1590/s0004-28032014000400012
|View full text |Cite
|
Sign up to set email alerts
|

IMMEDIATE PREOPERATIVE NUTRITIONAL STATUS OF PATIENTS WITH COLORECTAL CANCER: a warning

Abstract: -Context -Weight loss and malnutrition are disorders observed in colorectal cancer patients. Objetives -We sought to evaluate the immediate preoperative nutritional status of patients with colorectal cancer. Methods -This is a cross-sectional clinical study conducted at a single center. Sixty-six consecutive patients in preoperative for elective surgical treatment were studied. The clinical history, socio-demographic data and nutritional status of the patients were evaluated using Subjective Global Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
3
19
1
1
Order By: Relevance
“…Percentage weight loss is included as it is part of the criteria that is used to define malnutrition 22 and has universally been used as a prognostic variable for predicting post-operative outcome. 6 Handgrip strength was measured by using the non-dominant hand (Takei 5001 Grip Dynamometer Analogue). Three measurements were taken and the mean recorded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Percentage weight loss is included as it is part of the criteria that is used to define malnutrition 22 and has universally been used as a prognostic variable for predicting post-operative outcome. 6 Handgrip strength was measured by using the non-dominant hand (Takei 5001 Grip Dynamometer Analogue). Three measurements were taken and the mean recorded.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate percentage weight loss, the participants were asked to recall their previous weight (3–6 months ago); this was used with actual weight recorded at all time points to determine percentage weight loss. Percentage weight loss is included as it is part of the criteria that is used to define malnutrition and has universally been used as a prognostic variable for predicting post‐operative outcome . Handgrip strength was measured by using the non‐dominant hand (Takei 5001 Grip Dynamometer Analogue).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbosa et al [14] showed that 36.4% of patients with colorectal cancer (CRC) were malnourished preoperatively. van Stijn et al [15] performed a systematic review over 10 years to assess the role of evaluation of preoperative nutrition parameters in predicting postoperative outcomes in elderly patients.…”
Section: Nutritional Assessmentmentioning
confidence: 99%
“…Reports have indicated that the prevalence of hospital malnutrition is as high as 50% in HICs and approximately 70% in LMICs . Studies in LMICs show that the prevalence of pre‐operative malnutrition among surgical patients is also high (Table ) . Of these studies, 16 were from Latin American countries, 7 from China, 3 from Vietnam, 3 from Turkey, 2 from India and 1 from Thailand.…”
Section: Resultsmentioning
confidence: 99%